Weetzie Bat - Block, Francesca Lia. (New York : HarperCollins, 1989)
Follows the wild adventures of Weetzie Bat and her Los Angeles punk friends, Dirk, Duck-Man, and Secret-Agent-Lover Man.
"A Charlotte Zolotow book.".
Notable/Best Books (A.L.A.).
Publisher's Weekly.
Wilson's Senior High School.
Young Adult
Keywords: Punk culture -- Fiction; Punk culture -- Fiction; Los Angeles (Calif.) -- Fiction; Los Angeles (Calif.) -- Fiction